2018
DOI: 10.1002/lt.24979
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplantation in adults with liver disease due to common variable immunodeficiency leads to early recurrent disease and poor outcome

Abstract: Common variable immunodeficiency (CVID) is the most common form of primary immunodeficiency characterized by antibody deficiency, recurrent bacterial infections, and autoimmunity. Advanced chronic liver disease occurs in a subset of patients with CVID and manifests with various histological features, such as nodular regenerative hyperplasia, inflammation, fibrosis, and cholangiopathy. We present a case series characterizing the outcomes in adult patients transplanted for primary CVID-related liver disease. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 29 publications
2
39
0
Order By: Relevance
“…Subsequent biopsies were overshadowed by cholangiopathy. This is in line with the early manifestation of NRH in CVID-related liver disease described by Azzu et al (1)…”
Section: Patientsupporting
confidence: 91%
See 1 more Smart Citation
“…Subsequent biopsies were overshadowed by cholangiopathy. This is in line with the early manifestation of NRH in CVID-related liver disease described by Azzu et al (1)…”
Section: Patientsupporting
confidence: 91%
“…We read with interest the description from Azzu et al (1) of 4 cases of liver transplantation for nodular regenerative hyperplasia secondary to common variable immunodeficiency (CVID)-related liver disease. The authors describe overall poor outcomes with liver disease recurrence and infectious complications.…”
Section: To the Editormentioning
confidence: 99%
“…Noteworthy, histological examination showed NRH changes and cholestasis in all three patients undergoing post-transplant biopsy, as already previously described in non-immunodeficiency subjects (144). After a revision of literature data, including 18 patients, the authors found that CVID patients undergoing LT had a higher mortality compared to LT in general population, with only 55% subjects alive after 3-5 years of post-transplant follow-up (138). Moreover, CVID patients undergoing LT due to CVID-related liver disease (namely NRH) exhibited a worse 5-year survival compared to CVID patients who received LT for any cause (mainly chronic viral hepatitis) (138).…”
Section: Therapeutic Perspectives: Liver Transplantation and Hsctmentioning
confidence: 99%
“…On the other hand, the theoretical increase of infectious and neoplastic risk related to the long-term concomitant immunosuppressive therapy has historically determined a reluctance to perform LT in CVID patients. In the last decade, a growing number of reports described the outcome of LT performed in adult and pediatric CVID patients with viral hepatitis or NRH (137)(138)(139)(140)(141)(142)(143).…”
Section: Therapeutic Perspectives: Liver Transplantation and Hsctmentioning
confidence: 99%
See 1 more Smart Citation